Centralized Coordination of Decentralized Assistance for Patients with Gestational Trophoblastic Disease in Brazil A Viable Strategy for Developing Countries - Braga, Antonio; Burla, Marcelo; Freitas, Fernanda; Uberti, Elza; Viggiano, Mauricio; Sun, Sue Yazaki; Maesta, Izildinha; Elias, Kevin M.; Berkowitz, Ross S.; Brazilian Network Gestational Trop (Sci Printers & Publ Inc, 2016)
OBJECTIVE: To report on the Brazilian Association of Gestational Trophoblastic Disease's (GTD) formation of a network of regional care at specialized centers for women with GTD. STUDY DESIGN: We developed a questionnaire composed of 15 questions, which was sent by email to the 38 Brazilian GTD Reference Center (BGTDRC) Directors who are members of the Brazilian Association of GTD, in order to characterize the professionals involved in the care of patients with GTD and the type of assistance provided. RESULTS: The Directors of the BGTDRCs are usually specialists in Gynecology and Obstetrics (97%), with a median experience of a decade in treating women with GTD. The BGTDRCs are linked to university hospitals in 75% of centers and provide completely free medical care in 87%. However, 52% of centers do not perform chemotherapy in their reference center, and patients are referred elsewhere for chemotherapy. Despite some difficulties, the rate of patients lost to follow-up before human chorionic gonadotropin remission is 9%, and the GTD mortality rate is 0.9%. CONCLUSION: Due to large regional disparities, the BGTDRCs are not uniformly organized. However, under the coordination of the Brazilian Association of GTD there is now strong communication and collaboration among reference centers, which has significantly advanced both patient care and research into the management of these diseases.
Keywords: Brazil; chemotherapy; gestational trophoblastic disease; gestational trophoblastic neoplasia; hydatidiform mole; molar pregnancy